Developmental changes in endothelium-dependent vasodilation and the influence of superoxide anions in perinatal rabbit pulmonary arteries - Morecroft, Ian (1998)
1. ACh-induced vasodilation was investigated in pulmonary arteries from 8 and 2 day pre-term foetal, neonatal (0–12 h and 4 day old) and adult rabbits. The effects of superoxide anion generation [with hypoxanthine (HX, 0.1 mM)/xanthine oxidase (XO, 15 mu ml(−1))], endogenous superoxide dismutase (SOD) inhibition [with the Cu-Zn SOD inhibitor triethylenetetramine (TETA, 1 mM)], endogenous superoxide anion scavenging [by superoxide dismutase (SOD, 50 u ml(−1))] and inhibition of endothelial nitric oxide synthase (eNOS) [with, N(ω)-nitro-L-arginine methylester (L-NAME, 0.1 mM)], on basal and ACh-induced NO activity were studied by examining phenylephrine-induced contraction and ACh-induced vasodilation respectively. 2. L-NAME and endothelium removal abolished all ACh-induced vasodilation and 1 μM sodium nitroprusside fully dilated all vessels. ACh-induced vasodilation was absent in the 8 day pre-term foetus and 0–12 h neonate but present at all other ages. L-NAME itself contracted 2 day pre-term foetal vessels. At 0–12 h, SOD, but not the phosphodiesterase 5 inhibitor zaprinast (1 μM), uncovered ACh-induced vasodilation. At this age SOD reduced phenylephrine-induced contraction which was not influenced by TETA, L-NAME or HX/XO, and L-NAME itself did not cause contraction. This suggests both ACh-induced and basal NO activity are compromise in these vessels by endogenous superoxide anion production and deficiencies in endogenous SOD activity. 3. In 4 day vessels, but not adult vessels, L-NAME, TETA and HX/XO augmented contractions to phenylephrine, and L-NAME itself induced vasoconstriction, suggesting that basal NO and SOD activities were present by 4 days but were not evident in the adult. ACh-induced NO activity, and the influence of endogenous SOD on this, were present in the adult (and 4 day) vessels as superoxide generation with HX/XO significantly reduced ACh-induced vasodilation and this effect was inhibited by SOD and augmented by TETA. 4. Increased oxygen tensions >500 mmHg attenuated ACh-induced vasodilation in the foetal but not neonatal rabbits. Raising the oxygen tension from ∼20 to ∼120 mmHg revealed ACh-induced vasodilation in the 8 day pre-term vessels. 5. In summary, superoxide anion accumulation combined with deficiencies in SOD activity may transiently compromise basal and ACh-induced NO activity at birth. Experimental oxygen tensions markedly influence ACh-induced vasodilation in foetal rabbit pulmonary arteries.